A Behavioral Theory of Market Expansion Based on the Opportunity Prospects Rule - Barreto, Ilídio (Organization Science, 2012)
What explains organizational search and choice when multiple opportunities are available to the decision makers? Drawing on the behavioral view of the firm, and on the attention-based view, this study proposes a theoretical model centered on the opportunity prospects rule to explain market expansion, defined as the extent (how many) and the selection (which) of multiple available opportunities that are actually pursued by competing firms. We test our model using longitudinal, fine-grained data on commercial banks undertaking more than 1,300 opportunity choices. The findings show that firms do use the opportunity prospects rule when exercising market expansion choices and that slack and performance feedback moderate the effects of opportunity prospects. This paper contributes to organizational decision-making research and to the behavioral view of the firm by showing the importance of considering an opportunity-driven approach, by demonstrating the relevance of simplifying rules to explain the search for the consequences of alternatives, by extending recent efforts to provide a more forward-looking perspective to model organization behavior, and by showing when slack and performance feedback moderate the effects on market expansion of the opportunity prospects rule.